The emotional brain and the guilty mind : novel paradigms of culpability and punishment - Coppola, Federica (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book seeks to reframe the normative narrative of the 'culpable person' in American criminal law through a more humanising lens. It embraces such reframed narrative to revise the criteria of the current voluntarist architecture of culpability and advance a paradigm of punishment that positions social rehabilitation as its core principle. The book constructs this narrative by considering behavioural and neuroscientific insights into the functions of emotions, and socio-environmental factors within moral behaviour in social settings. Hence, it suggests culpability notions that reflect a more contextualised view of human conduct, and argues that such revised notions are better suited to the principle of personal guilt. Furthermore, it suggests a model of 'punishment' that values the dynamic power of change of individuals, and acknowledges the importance of social relationships and positive environments to foster patterns of social (re)integration. Ultimately, this book argues that the potential adoption of the proposed models of culpability and punishment, which view people through a more comprehensive lens, may be a key factor for turning criminal justice into a less punitive, more inclusionary and non-stigmatising system"--
The rationalist soul of culpability : an analysis of the guilty mind -- From the guilty mind to the punished person : criminal culpability through the 'evolution' of punishment -- Critiques of the model of the 'person' in culpability and punishment -- Emotions, the social environment, and the brain -- Holistic and situated culpability -- Social rehabilitation.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Guilt (Law); Punishment; Criminal liability; Criminal law; Emotions -- Psychological aspects; Criminology: legal aspects; Electronic books